Substitution of social concerns under the Covid-19 pandemic - Esther Blanco; Alexandra Baier; Felix Holzmeister; Tarek Jaber-Lopez; Natalie Struwe (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Think tanks and political leaders have raised concerns about the implications that the Covid-19 response and reconstruction might have on other social objectives that were setting the international agenda before the Covid-19 pandemic. We present experimental evidence for eight consecutive weeks during April-May 2020 for Austria, testing the extent to which Covid-19 concerns might substitute other social concerns such as the climate crisis or the protection of vulnerable sectors of the society. We measure behavior in a simple donation task where participants receive Euro 3 that they can distribute between themselves and different charities. While participants in one treatment have the opportunity to donate, if any, to eight different charities including a rich set of social concerns (Baseline), participants in a second treatment can choose to donate, if any, to the same charities and, in addition, to the Covid-19 Solidarity Response Fund for the World Health Organization (Covid-19). In a third treatment, participants can only decide on distributing the Euro 3 between themselves and the Covid-19 Solidarity Response Fund (Covid-19 Only). Our results show that introducing the Covid-19 Solidarity Response Fund does not significantly change aggregate donations (donations represent 76.3% of endowment in Baseline and 70.2% in Covid-19, t(584) = 1.938, p = 0.053, n = 585). But, given positive donations to the Covid19 Solidarity Response Fund, this entails significantly lower donations to the other eight charities (76.3% in Baseline and 60.8% in Covid-19, t(584) = 5.868, p < 0.001, n = 585). Moreover, our results point to a high support to the WHO Covid-19 Fund: In the treatment where the WHO Covid-19 Fund is the only available recipient, participants donate about 50% of their endowment (Covid-19 Only), while in the treatment where it is one out of nine recipients, donations are still 9.5% of endowment (Covid-19) . Overall, our results indicate that donations to diverse social concerns are partially substituted by donations to the Covid-19 fund; yet, this substitution is far from replacing all other social concerns.
Keywords: L3; D64; Q54; I3; D9; 330; Charitable donation; Covid-19 pandemic; climate crisis; poverty; substitution of social concerns